Quantitative assessment of ecotourism in the National Park “Samarskaya Luka” - Sheldiasheva, Valeriia (2019)
This paper presents quantitative assessment of the territory in order to measure ecotourism in the National Park "Samarskaya Luka" in the Samara region. The aim of the study is to evaluate the potential sustainability in this National Park. A survey was conducted among stakeholders based on the previous study. The results were obtained using equations and calculations with a five-point Likert scale. The conclusion describes the importance of the developing of the ecotourism, as well as the main indicators and the relationships that need to be enhanced were identified. As well, as the aspects that reveal the potential of the region are highlighted. It has been established after measuring, that for the National park "Samarskaya Luka" the ecotourism is possible, and it can be used as a tool for economic development and preservation of the natural resources, since it is potentially sustainable. The work highlighted the needs of the Samara region in the future developing, considering the expected Eco education mechanisms. It justifies the need for ecotourism knowledge among local residents. A more detailed consideration of certain aspects of the relationships, with the help of a more spread survey of the population in the field of education in this aspect. The ecotourism dimension discussed in this paper can be used to improve the strategies of the tourism activities, and within the framework of the economic and environmental development of regions with a similar structure.